Therapeutic plasma exchange in gastric signet ring cell carcinoma presenting as microangiopathic hemolytic anemia: A rare case report - Candar, Omer; Ekinci, Omer; Merter, Mustafa; Aslan, Mehmet; Aras, Ibrahim (Wiley, 2022)
Microangiopathic hemolytic anemia (MAHA) defines a group of disorders characterized by the formation of microthrombi in capillaries and arterioles and the fragmentation of erythrocytes that pass through. Cancer-related MAHA is a rare but serious condition that is encountered in patients diagnosed with a malignancy. This clinical picture is thought to be linked to certain tumor characteristics; particularly, adenocarcinoma histology, vascular invasion, and bone marrow infiltration. MAHA is most commonly associated with tumors of gastric, prostate, and breast origin. The optimal treatment is not clear; however, there is evidence for the importance of promptly starting an effective antineoplastic regimen and it was also reported that administering therapeutic plasma exchange (TPE) therapy for immunocomplex removal could be beneficial for patients with symptoms of bleeding and thrombosis. Here, we present a case that presented a picture of MAHA secondary to gastric signet-ring cell adenocarcinoma (SRCC). The clinical picture was initially evaluated as thrombotic thrombocytopenic purpura and the patient benefited significantly from the TPE treatment administered before the adenocarcinoma diagnosis was confirmed. In this period, epistaxis stopped, platelet count increased from 25 x 10(9)/L to 162 x 10(9)/L, fragmented erythrocyte rate in the peripheral smear decreased by more than 75% and other laboratory findings of hemolysis (LDH, bilirubin, etc.) significantly improved.
Keywords: gastric carcinoma; microangiopathic hemolytic anemia; signet ring cell carcinoma; therapeutic plasma exchange; thrombotic microangiopathy